Features of 847 Childhood-Onset Systemic Lupus Erythematosus Patients in Three Age Groups at Diagnosis: A Brazilian Multicenter Study - Gomes, Roberta C.; Silva, Marco F.; Kozu, Katia; Bonfá, Eloisa; Pereira, Rosa M.; Terreri, Maria T.; Magalhães, Claudia S. [UNESP]; Sacchetti, Silvana B.; Marini, Roberto; Fraga, Melissa; Carvalho, Luciana M.; Barbosa, Cássia M.; et al. (Wiley, 2016)
Objective: To evaluate demographic data and clinical and laboratory features at disease diagnosis in 3 different age groups of childhood-onset systemic lupus erythematosus (SLE): group A, early-onset (<6 years); group B, school age (≥6 to <12 years); and group C, adolescent (≥12 to <18 years). Methods: This was a Brazilian multicenter cohort retrospective study in 10 pediatric rheumatology centers, including 847 childhood-onset SLE patients. Results: Patients were divided into 3 groups: group A with 39 patients (4%), group B with 395 patients (47%), and group C with 413 patients (49%). Of 39 childhood-onset SLE patients in group A, 3 (8%) were ages <2 years, 4 (10%) were ≥2 to <3 years, and 32 (82%) were ≥3 and <6 years. A total of 74 childhood-onset SLE patients were analyzed for C1q levels, and complete C1q deficiency was observed in 3 of 74 patients (4%), all in group A. Groups were similar regarding high frequencies of female sex, nephritis, neuropsychiatric involvement, Systemic Lupus Erythematosus Disease Activity Index 2000 score ≥8, autoantibody profile, elevated acute phase proteins, and low complement levels (P > 0.05). However, the frequency of fever (78% versus 61% versus 47%; P < 0.0001), hepatomegaly (42% versus 29% versus 14%; P < 0.0001), splenomegaly (28% versus 12% versus 4%; P < 0.0001), and discoid lupus (13% versus 4% versus 4%; P = 0.020) was significantly higher in group A compared to groups B and C. The frequency of weight loss >2 kg (19% versus 28% versus 36%; P = 0.017), photosensitivity (34% versus 41% versus 51%; P = 0.006), leukopenia <4,000/mm3 (14% versus 25% versus 30%; P = 0.048), and lymphopenia <1,500/mm3 (22% versus 41% versus 47%; P = 0.011) was significantly lower in group A. Conclusion: Our large multicenter study identified the finding that the initial appearance of childhood-onset SLE is characterized by comparable high frequency of internal organ involvement and some distinct clinical and laboratory features in early-onset and adolescent groups.